2020
DOI: 10.1007/s00417-020-04763-z
|View full text |Cite
|
Sign up to set email alerts
|

Emulsified silicone oil is taken up by and induces pro-inflammatory response in primary retinal microglia

Abstract: Purpose Silicone oil is used as endotamponade in combination with vitrectomy. Thinning of retinal layers and loss of retinal cells under silicone oil use have been found. Here, we investigate the influence of silicone oil on primary microglia cells. Methods Primary microglia cells were prepared from the porcine retina. Microglia identity was assessed with Iba1 staining. Silicone oil was emulsified by sonification. Cell morphology and silicone oil uptake were evaluated by light microscopy after Coomassie blue s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 31 publications
2
11
0
Order By: Relevance
“…The toxicity of SO to the retinal neurons might be an explanation and had been widely discussed [ 11 , 36 , 37 ]. The inner retina is in direct contact with SO, and experimental evidence in vitro has shown that emulsified SO can be taken up by primary retinal microglia, where it induces a pro-inflammatory response [ 38 ]. Studies with enucleated eyes applied with SO tamponade confirmed that intraretinal macrophages contained phagocytosed SO, and the eccentric pigment granules were present in the superficial retina [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The toxicity of SO to the retinal neurons might be an explanation and had been widely discussed [ 11 , 36 , 37 ]. The inner retina is in direct contact with SO, and experimental evidence in vitro has shown that emulsified SO can be taken up by primary retinal microglia, where it induces a pro-inflammatory response [ 38 ]. Studies with enucleated eyes applied with SO tamponade confirmed that intraretinal macrophages contained phagocytosed SO, and the eccentric pigment granules were present in the superficial retina [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested that SO can induce intraocular inflammation and retinal toxicity, which may also contribute to poor visual recovery in eyes with an extended course of SO in situ. 21–23 Because almost 95% of the cohort was pseudophakic at the final follow-up visit, cataract progression had minimal impact on visual acuity outcomes in this study. Ultimately, the removal of SO is a clinical decision tailored to each patient's clinical scenario and the presence of any complications.…”
Section: Discussionmentioning
confidence: 96%
“…Nevertheless, these changes did not reach the level of statistical significance ( p = 0.44) [ 42 ]. In addition, the inner retinal layers were shown to be much thinner in the presence of SO tamponade in comparison to healthy eyes in two separate tests that were carried out by Purtskhvanidze et al and Caramoy et al [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%